Detection of Trojan Asteroids in the orbits of Earth and Mars - Todd, Michael Anthony (Curtin University, 2014)
This work describes probability distributions and constrains sky search areas for Earth and Mars Trojan asteroids, proposes search strategies using ground-based telescopes and predicts outcomes from the Gaia mission for detection of Earth and Mars Trojans, describes the role of the Zadko Telescope as part of the Gaia Follow-Up Network for Solar System Objects and the development of the High Efficiency Image Detection & Identification (HEIDI) pipeline software to rapidly analyse time series image data.